Driving next-generation autophagy researchers towards translation (DRIVE), an international PhD training program on autophagy - Claudine Kraft; Patricia Boya; Patrice Codogno; Zvulun Elazar; Eeva-Liisa Eskelinen; Judith Farrés; Vladimir Kirkin; Heinz Jungbluth; Ana Martinez; Ole Pless; Charlotte Primard; Tassula Proikas-Cezanne; et al. (My University, 2022)
The European autophagy consortium Driving next-generation autophagy researchers towards translation (DRIVE) held its kick-off meeting in Groningen on the 14th and 15th of June 2018. This Marie Skłodowska-Curie Early Training Network was approved under the European Union's Horizon 2020 Research and Innovation Program and is funded for 4 years. Within DRIVE, 14 European research teams from academia and industry will train 15 PhD students through applied, cross-disciplinary and collaborative macroautophagy/autophagy research. The goal of DRIVE is to stimulate applied approaches in autophagy research and provide training towards translation, while advancing our knowledge on autophagy in specific physiological and pathological states. The strong focus on translation will prepare the PhD students to be at the forefront to exploit autophagy for the development of therapies directly benefitting patients. Thereby, DRIVE will contribute to filling the educational gap that currently exists between academia and industry, and will prepare its PhD students for alternative and highly flexible professional paths